Alzheimer's disease neurofibrillary degeneration: pivotal and multifactorial. (26th July 2010) - Iqbal, Khalid; Wang, Xiaochuan; Blanchard, Julie; Liu, Fei; Gong, Cheng-Xin; Grundke-Iqbal, Inge
Abstract : Independent of the aetiology, AD (Alzheimer's disease) neurofibrillary degeneration of abnormally hyperphosphorylated tau, a hallmark of AD and related tauopathies, is apparently required for the clinical expression of the disease and hence is a major therapeutic target for drug development. However, AD is multifactorial and heterogeneous and probably involves several different aetiopathogenic mechanisms. On the basis of CSF (cerebrospinal fluid) levels of Aβ 1–42 (where Aβ is amyloid β-peptide), tau and ubiquitin, five different subgroups, each with its own clinical profile, have been identified. A successful development of rational therapeutic disease-modifying drugs for AD will require understanding of the different aetiopathogenic mechanisms involved and stratification of AD patients by different disease subgroups in clinical trials. We have identified a novel aetiopathogenic mechanism of AD which is initiated by the cleavage of SET, also known as inhibitor-2 (I2 PP2A ) of PP2A (protein phosphatase 2A) at Asn 175 into N-terminal (I2NTF ) and C-terminal (I2CTF ) halves and their translocation from the neuronal nucleus to the cytoplasm. AAV1 (adeno-associated virus 1)-induced expression of I2CTF in rat brain induces inhibition of PP2A activity, abnormal hyperphosphorylation of tau, neurodegeneration and cognitive impairment in rats. Restoration of PP2A activity by inhibition of the cleavage of I2 PP2A /SET offers a promising therapeutic opportunity in AD with this aetiopathogenic mechanism.